Polish and Finnish students’ views on andropause. Part II. The image of a menopausal woman and an andropausal man - Pryczek, Katarzyna; Bielawska-Batorowicz, Eleonora (Menopause Review/Przegląd Menopauzalny, 2008)
Aim: To describe the image of an andropausal man and a menopausal woman among Polish and Finnish students and analyze the impact of knowledge about andropause on that image. The study was designed as cross-sectional and all measures were taken at the same time. Material and methods: 224 students from Łódź and Tampere participated in the study. The Polish sample included 62 females and 54 males, and the Finnish sample included 62 females and 46 males. Two questionnaires were administered: “The description of a man/a woman” and “Andropausal symptoms”. Both were designed for the study in Polish and Finnish language versions. Results: Univariate analyses indicated significant differences in the image of an andropausal man among Polish and Finnish students, with Finns expressing more positive views. Differences between men’s and women’s views were not significant. The image of a menopausal woman was not affected by the gender or nationality of respondents. Multivariate analysis indicated the effect of gender – females described a menopausal woman more positively, while males described an andropausal man more positively. Men’s views on a menopausal woman were more positive than women’s views on an andropausal man. Knowledge on andropause affected the image of a man – male students who expressed more knowledge perceived an andropausal man more negatively. The same, but non-significant, tendency was observed among female students. The images of a menopausal woman and an andropausal man were highly correlated. Conclusions: In the images of andropausal men and menopausal women the negative elements outnumbered positive ones. The images were highly correlated. That can be interpreted as a tendency towards unified perception and evaluation of persons in similar age groups regardless of their gender.